Computational modeling of objects presented in images : fundamentals, methods, and applications : 5th International Symposium, CompIMAGE 2016, Niagara Falls, NY, USA, September 21-23, 2016, Revised selected papers /: fundamentals, methods, and applications : 5th International Symposium, CompIMAGE 2016, Niagara Falls, NY, USA, September 21-23, 2016, Revised selected papers. (2017) - Unknown
No abstract available